Ginsenoside Rg1 and Rb1, in combination with salvianolic acid B, play different roles in myocardial infarction in rats. Issue 2 (February 2015) - Deng, Yanping; Zhang, Tingting; Teng, Fukang; Li, Defang; Xu, Feng; Cho, Kenka; Xu, Jinghua; Yin, Jun; Zhang, Li; Liu, Qian; Yang, Ming; Wu, Wanying; et al.
Abstract : Background : The herb pair of Salvia miltiorrhiza and Panax notoginseng has widely been used for improving coronary and cerebral circulation in China. However, the exact contribution of the major active components of S. miltiorrhiza and P. notoginseng to cardioprotection is far from clear. In the present study, three representative ingredients, salvianolic acid B (SalB) from S. miltiorrhiza and ginsenoside Rg1 (Rg1) and ginsenoside Rb1 (Rb1) from P. notoginseng, were selected to elucidate the mechanism of the herb pair at the ingredient level. Methods : The purity of SalB, Rg1, and Rb1 was >99%, as detected by high‐performance liquid chromatography. Acute myocardial infarction was introduced by ligation of the left anterior descending coronary artery near the main pulmonary artery. Cardiac contractility was detected through a Mikro‐tipped catheter, and cardiac infarct size was determined using triphenyltetrazolium chloride stain. Results : The combination of SalB and Rg1, and not the combination of SalB and Rb1, improved heart contractility in rats with myocardial infarction. The different contributions of Rg1 and Rb1, in combination with SalB, to cardioprotection provides further direction to optimize and modernize the herbal medicines containing S. miltiorrhiza and P. notoginseng . Conclusion : The combination of SalB and Rg1 may provide potential protection against myocardial infarction.